An overview of configurable computing machines for software radio handsets. - Srikanteswara, S. (IEEE Communications magazine)
The advent of software radios has brought a paradigm shift to radio design. A multimode handset with dynamic reconfigurability has the promise of integrated services and global roaming capabilities. However, most of the work to date has been focused on software radio base stations, which do not have as tight constraints on area and power as handsets. Base station software radio technology progressed dramatically with advances in system design, adaptive modulation and coding techniques, reconfigurable hardware, A/D converters, RF design, and rapid prototyping systems, and has helped bring software radio handsets a step closer to reality. However, supporting multimode radios on a small handset still remains a design challenge. A configurable computing machine, which is an optimized FPGA with application-specific capabilities, show promise for software radio handsets in optimizing hardware implementations for heterogeneous systems. In this article contemporary CCM architectures that allow dynamic hardware reconfiguration with maximum flexibility are reviewed and assessed. This is followed by design recommendations for CCM architectures for use in software radio handsets.